Fate of floating plastic debris released along the coasts in a global ocean model. (April 2021) - Chenillat, Fanny; Huck, Thierry; Maes, Christophe; Grima, Nicolas; Blanke, Bruno
Abstract: Marine plastic pollution is a global issue, from the shores to the open ocean. Understanding the pathway and fate of plastic debris is fundamental to manage and reduce plastic pollution. Here, the fate of floating plastic pollution discharged along the coasts is studied by comparing two sources, one based on river discharges and the other on mismanaged waste from coastal populations, using a Lagrangian numerical analysis in a global ocean circulation model. About 1/3 of the particles end up in the open ocean and 2/3 on beaches. The input scenario largely influences the accumulation of particles toward the main subtropical convergence zones, with the South Pacific and North Atlantic being mostly fed by the coastal population inputs. The input scenario influences the number of beached particles that end up in several coastal areas. Beaching occurs mainly locally, although a significant number of particles travel long distances, allowing for global connectivity. Highlights: Rivers and coastal populations are key sources of marine plastic pollution. This pollution accumulates at the coasts (~2/3) and on the open ocean (~1/3). Littering of coastal populations explains better the pollution of subtropical gyres. Floating debris can travel long distances (up to several thousand kilometers). Long-distance floating debris allows connectivity between remote coastal regions.